Novel Method for the Separation of Male and Female Gametocytes of the Malaria Parasite Plasmodium falciparum That Enables Biological and Drug Discovery - Melanie C. Ridgway (American Society for Microbiology, 2020)
ABSTRACT We developed a flow-cytometry-based method to separate and collect cocultured male and female Plasmodium falciparum gametocytes responsible for malaria transmission. The purity of the collected cells was estimated at >97% using flow cytometry, and sorted cells were observed by Giemsa-stained thin-smear and live-cell fluorescence microscopy. The expression of validated sex-specific markers corroborated the sorting strategy. Collected male and female gametocytes were used to confirm three novel sex-specific markers by quantitative real-time PCR that were more enriched in sorted male and female gametocyte populations than existing sex-specific markers. We also applied the method as a proof-of-principle drug screen that allows the identification of drugs that kill gametocytes in a sex-specific manner. Since the developed method allowed for the separation of male and female parasites from the same culture, we observed for the first time a difference in development time between the sexes: females developed faster than males. Hence, the ability to separate male and female gametocytes opens the door to a new field of sex-specific P. falciparum gametocyte biology to further our understanding of malaria transmission. IMPORTANCE The protozoan Plasmodium falciparum causes the most severe form of human malaria. The development of sexual forms (so-called gametocytes) is crucial for disease transmission. However, knowledge of these forms is severely hampered by the paucity of sex-specific markers and the inability to extract single sex gametocytes in high purity. Moreover, the identification of compounds that specifically affect one sex is difficult due to the female bias of the gametocytes. We have developed a system that allows for the separation of male and female gametocytes from the same population. Applying our system, we show that male and female parasites mature at different rates, which might have implications for transmission. We also identified new sex-specific genes that can be used as sex markers or to unravel sex-specific functions. Our system will not only aid in the discovery of much needed gametocidal compounds, but it also represents a valuable tool for exploring malaria transmission biology.